Preparation method of high-thermal-conductivity radiation refrigeration composite film

Through the preparation method of the P-S-x composite film, the problem of poor effect in the cooling of internal heat source objects is solved, high thermal conductivity and effective radiation refrigeration are achieved, and the cooling ability of the cooled object is significantly improved.

CN119119533AInactive Publication Date: 2024-12-13CHINA THREE GORGES UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411352855.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-26
Publication Date
2024-12-13
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing radiation refrigeration materials do not work well in cooling objects with internal heat sources and are difficult to effectively cool down, especially traditional materials can only cool objects slightly below or close to the ambient temperature.

Method used

Using the preparation method of P-S-x composite membrane, ST is mixed with DMF and KH570 and dispersed under a cell crusher, PVDF powder is added and dissolved in a heated water bath, and then PDMS is added to a magnetic mixer to form a P-S-x composite membrane scraping solution , and by scraping and hot pressing forming, a P-S-x composite film film with high heat conductivity is formed.

Benefits of technology

The thermal conductivity and radiation cooling performance of the composite film are improved, so that it can effectively cool down under sun exposure. It is especially suitable for objects with internal heat sources, and the cooling effect is significantly better than that of traditional materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119119533A_ABST
    Figure CN119119533A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of films and radiation refrigeration, and particularly discloses a preparation method of a high-thermal-conductivity radiation refrigeration composite film, which comprises the following steps of: selecting polyvinylidene fluoride (PVDF) with high emission in an atmospheric window wave band as a polymer matrix material; strontium titanate (ST) powder with a high refractive index, a wide forbidden band coefficient and a high heat conductivity coefficient is selected as filling particles. The daytime radiation refrigeration performance of the composite film is optimized by adjusting the mass ratio of PVDF to ST and the thickness of the composite film, and the finally prepared composite film has the characteristics of high emissivity (2.5-25 microns) of middle and outer wave bands and high reflectivity of visible light-near infrared, has the characteristics of flexibility, high heat conductivity and the like, and can be widely applied to the field of high-temperature radiation refrigeration. Therefore, more cooling power can be provided for a cooled object (especially an object which is higher than the environment temperature and has an internal heat source).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of thin films and passive refrigeration, and in particular relates to a method for preparing a radiation cooling film with high thermal conductivity. Background Art

[0002] Solar radiation and the loss caused by equipment operation increase the surface and internal temperature of objects, especially in the summer when global temperatures are rising, which may affect the normal operation of equipment and even the personal safety of residents around it. Radiative cooling technology, which spontaneously dissipates heat into outer space through the atmospheric window (8-13 μm) without consuming any energy or releasing carbon dioxide, is promising because of its ease of use and scalability. At present, most researchers only create porous or filled dielectric particles to scatter sunlight on the basis of selective high-emission polymer materials to obtain high sunlight reflection ability to achieve radiative cooling performance. Few people design according to the application environment and usage scenario requirements. Radiative cooling materials with only high sunlight reflectivity and high atmospheric window emissivity (selective emitters) do not have obvious cooling effects on cooling objects with internal heat sources. For objects with internal heat sources, their temperature is often higher than the ambient temperature. At this time, compared with selective emitter materials, broadband emission materials (with high emissivity in the entire mid-infrared band) can provide more cooling power, and high-temperature substances always transfer energy to low-temperature substances. Increasing the thermal conductivity of radiative cooling materials can provide more cooling power for the cooled objects. In real life, traditional radiative cooling methods are often because the objects to be cooled usually have a large heat capacity and can only be cooled to a temperature slightly lower than or close to the environment, so the temperature of the cooled objects is higher than the ambient temperature most of the time. Therefore, how to prepare a radiative cooling material with high thermal conductivity has become a technical problem that technicians in this field urgently need to solve. Summary of the invention

[0003] The technical problem to be solved by the present invention is to provide a method for preparing a radiation refrigeration material with high thermal conductivity.

[0004] The technical solution adopted to solve the above technical problems is: a method for preparing a radiation cooling film, which includes two steps: preparing a PSx composite film coating liquid and forming a high thermal conductivity radiation cooling composite film (PSx composite film thin film).

[0005] First, ST was mixed with DMF and KH570 and dispersed in a cell crusher. Then, PVDF powder was added to the evenly dispersed ST dispersion and stirred and heated in a heated water bath to completely dissolve the PVDF powder in the ST dispersion. Finally, it was taken out and placed on a constant temperature heated magnetic stirrer, and a small amount of PDMS was added and stirred for 3-4 h to obtain an evenly dispersed PSx composite membrane coating solution.

[0006] The second step is to prepare the PSx composite film. The solution is scraped onto a clean substrate by blade coating. After curing on a heated aluminum table, it is placed in a hot press for hot pressing to finally obtain a PSx composite film with high thermal conductivity.

[0007] The mass ratio of NN dimethylformamide, KH570 and strontium titanate powder is 10:0.1-0.2:0.5-1.75; in some specific embodiments, the amount of strontium titanate powder is any one of 10:0.2:0.5, 10:0.2:1.0, 10:0.2:1.5, 10:0.2:1.75, denoted as PSx (x=0.5, 1.0, 1.5, 1.75); preferably, the mass ratio of NN dimethylformamide, KH570 and strontium titanate powder is 10:0.2:1.75 (PS-1.75).

[0008] The function of the KH570 is to reduce the agglomeration of strontium titanate powder and increase the compatibility with the polymer.

[0009] The dispersion is carried out in a cell crusher for 5-20 min. The working parameters of the cell crusher are stirring for 5 s, stopping for 5 s, and the total time is 5-20 min, preferably 10 min.

[0010] The mass ratio of the added amount of the PVDF powder to the strontium titanate powder is 0.5-1.75.

[0011] The PVDF powder is added to the strontium titanate dispersion while stirring to shorten its dissolution time and the drug residue on the container wall. The stirring speed is 200-500 r / min, the working temperature is 60-80°C, and the stirring time is 1-2 h.

[0012] The amount of PDMS added is 1% of the PVDF powder, wherein a small amount of PDMS is used to increase the adhesion of the composite film and further improve the flexibility of the composite film.

[0013] The substrate is a metal aluminum plate polished by sandpaper; the working temperature of the aluminum table is 80-90 ℃; the aluminum table is heated to allow the scraping liquid to solidify on the substrate. The working parameters of the hot press are 150-180 ℃, 8-10 MPa, 1-2 h. The hot press is used to reduce the pores in the composite film and increase the thermal conductivity of the composite film.

[0014] The beneficial effects of the present invention are as follows: the technical solution provided by the present application adopts two steps including the preparation of PSx composite film coating liquid and the molding of PSx composite film to prepare the radiation cooling composite film, wherein the molding of the PSx composite film is achieved by applying the prepared PSx composite film coating liquid onto the substrate, curing it on a heated aluminum table, and finally placing it in a hot press for hot pressing. The interface formed by ST and PVDF strongly scatters sunlight, so that the prepared PS-1.75 composite film has a high solar emissivity (R 0.45-2μm =84%), thereby reducing the absorption of sunlight energy by the cooled object; at the same time, the filling of ST transforms PVDF from a selective emitter to a broadband emitter (E 2.5-25 μm =97%), which improves the ability of the cooled object to emit heat into the air in the form of infrared microwaves, so that the cooling composite film has the function of cooling under sunlight; the filling of ST in the composite film constructs a heat conduction channel, which improves the overall thermal conductivity of the composite film (the thermal conductivity coefficient is 1.97 W / (m·K)), thereby further improving the cooling ability of the composite film for objects with a temperature higher than the ambient temperature (or with an internal heat source). BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 The SEM scanning electron micrographs of the surfaces of the PSx composite membranes prepared in Example 1 of the present invention are shown in Figure 1. (a) is a SEM scanning electron micrograph of the surface of the PS-0.5 composite membrane; (b) is a SEM scanning electron micrograph of the surface of the PS-1 composite membrane; (c) is a SEM scanning electron micrograph of the surface of the PS-1.5 composite membrane; and (d) is a SEM scanning electron micrograph of the surface of the PS-1.75 composite membrane.

[0016] Figure 2The optical parameter diagrams of PSx composite films with different ST contents and PS-1.75 composite films with different thicknesses prepared in Examples 1 and 2 of the present invention are shown. Among them, (a) is the reflectivity of PSx composite films with different ST contents; (b) is the emissivity spectrum of PSx composite films with different ST contents; (c) is the average reflectivity and emissivity of PSx composite films with different ST contents; (d) is the reflectivity of PS-1.75 composite films with different thicknesses; (e) is the emissivity of PS-1.75 composite films with different thicknesses; (f) is the average reflectivity and emissivity of PS-1.75 composite films with different thicknesses; (g) is the reflectivity of PS-1.75 composite films with a thickness of ~115 μm and PVDF film in the sunlight band; (h) is the emissivity of PS-1.75 composite films with a thickness of ~115 μm and PVDF film in the mid-infrared band.

[0017] Figure 3 The outdoor photos and flexibility performance tests of the PS-1.75 composite film prepared in Example 1 of the present invention are shown in Figure 1. (a) is an outdoor photo of PS-1.75; (b) to (d) are folding and curling flexibility tests of the PS-1.75 composite film.

[0018] Figure 4 The SEM images of PS-1.75 composite films of different thicknesses prepared in Example 2 of the present invention are shown in FIG. (a) is the thickness of the PS-1.75 composite film prepared when the thickness of the scraping solution is 500 μm; (b) is the thickness of the PS-1.75 composite film prepared when the thickness of the scraping solution is 1000 μm; (c) is the thickness of the PS-1.75 composite film prepared when the thickness of the scraping solution is 1500 μm; and (d) is the thickness of the PS-1.75 composite film prepared when the thickness of the scraping solution is 2000 μm.

[0019] Figure 5 The finite element analysis thermal conductivity simulation diagram of the PS-1.75 composite film and the PVDF film prepared in Example 2 of the present invention. Among them, (a) is a schematic diagram of the finite element analysis simulation of the PS-1.75 composite film and the PVDF film; (b) The temperature of the PS-1.75 composite membrane and the PVDF membrane changes with the heat transfer (simulation) time at a distance of 2.5 cm from the heat source; (c) The surface temperature of the PS-1.75 composite membrane changes with the heat transfer time and propagation depth; (d) is the top view of (c); (e) is the surface temperature of the PVDF composite membrane changes with the heat transfer time and propagation depth; (f) is the top view of (e).

[0020] Figure 6The summer cooling effect diagram of the PS-1.75 composite membrane and PVDF film prepared in Example 2 of the present invention. Among them, (a) is the test device model and side anatomical diagram and the actual photo of the outdoor cooling test device. (b) is the temperature change curve of the surface and sub-environment of all test samples in the time period of 10:30-14:00. (c) The temperature difference of the surface of all test samples relative to the surface of Al. (d) is the temperature difference of the surface of all test samples relative to the sub-environment. Figure 6 (e) Temperature variation curves of the chamber and sub-environment of all test samples during the period of 10:30-14:00. (f) Temperature difference of the chamber of all test samples relative to that of Al. (g) Temperature difference of the chamber of all test samples relative to the sub-environment.

[0021] Figure 7 The following is a graph showing the summer cooling effect of the PS-1.75 composite film prepared in Example 2 of the present invention compared with commercial white paint. (a) is the surface, cavity interior and sub-ambient temperature curves of all test samples; (b) is the surface and cavity temperature difference of all test samples relative to the Al sample.

[0022] Figure 8 The temperature drop performance of the PS-1.75 composite film prepared in Example 2 of the present invention in the application scenario of an outdoor electric vehicle charger. Among them, (a) is a real photo of an outdoor electric vehicle charger partially covered by a PS-1.75 composite film; (b) is a thermal infrared image of the initial temperature of point P1 covered by the PS-1.75 composite film and point P2 uncovered when the charger is not exposed to sunlight. (c) is a thermal infrared image of the temperature of point P1 and P2 at 0 minutes, 1 minute, 5 minutes, 8 minutes and 15 minutes of exposure to the sun; (d) is a thermal infrared image of the temperature of point P1 and P2 after 0 seconds, 1 second, 5 seconds, 8 seconds and 15 seconds after removing the PS-1.75 composite film. DETAILED DESCRIPTION

[0023] The present invention is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several variations and improvements may be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.

[0024] Example 1 The present invention conducts experiments on PVDF / ST radiative cooling composite films doped with different ST contents, and the specific methods are as follows: (1) Take 10 g of NN dimethylformamide, 0.2 g of KH570, and x g (x = 0.5, 1, 1.5, 1.75) of strontium titanate powder, place them in a container for mixing, and use a cell crusher to disperse them for 10 min to prepare a strontium titanate dispersion.

[0025] (2) Weigh 1 g of PVDF and add it to the strontium titanate dispersion under magnetic stirring. Then heat it in a water bath at 300 r / min and 60 °C for 1.5 h to dissolve it.

[0026] (3) Finally, move it to a magnetic stirrer, add a small amount of PDMS (1 wt%), and stir at 800 r / min and 60 °C for 4 h to obtain a PSx composite film coating liquid.

[0027] (4) Adjust the coating film thickness and apply the coating liquid onto the aluminum substrate that has been polished by sandpaper.

[0028] (5) Heat the aluminum heating table to 90 °C and place the scraped sample on it to allow it to cure for about 15 min.

[0029] (6) The cured samples were transferred to a hot press and heated at 10 MPa and 180 °C for 2 h to form PSx composite films, which were named PS-0.5, PS-1, PS-1.5, PS-1.75 and PS-2 composite films respectively.

[0030] In addition, pure PVDF film was prepared by the same preparation method as above and used as a control group.

[0031] Figure 1 This is a SEM scanning electron microscope image of the PSx composite membrane prepared in Example 1 of the present invention. Figure 1 It can be seen that with the increase of ST filling amount, some ST particles agglomerate, but there are almost no cracks and holes on the surface of PSx film. The aggregation of ST particles and the uneven distribution on the film surface also lead to the roughness and unevenness of PSx film surface, which may increase the reflectivity of the composite film.

[0032] Figure 2 (a)-(c) are optical performance diagrams of the PSx composite film prepared in Example 1 of the present invention. Figure 2 (a) and Figure 2As can be seen in (c), when x increases from 0.5 to 1.75, the average reflectivity of the composite film (0.5-2.0 μm) increases from 70% to 79%, among which the average reflectivity of the PS-1.75 composite film is the highest. The increase in the reflectivity of the composite film may be due to the high refractive index contrast between ST and PVDF, which has a strong scattering effect on sunlight. As x increases, the average emissivity of the PSx composite film increases from 95% to 97%, and the change is not significant.

[0033] Figure 3 The outdoor photos and flexibility test of the PS-1.75 composite film prepared in Example 1 of the present invention. Figure 3 We can see that the composite film has a bright white color and it also has considerable flexibility.

[0034] Example 2 The present invention has carried out the experiment to the thickness of PS-1.75 radiation refrigeration composite film, and the specific method is as follows: (1) Take 10 g of NN dimethylformamide, 0.2 g of KH570, and 1.75 g of strontium titanate powder, place them in a container for mixing, and disperse them using a cell crusher for 10 min to prepare a strontium titanate dispersion.

[0035] (2) Weigh 1.75 g of PVDF and add it to the strontium titanate dispersion under magnetic stirring. Then heat it in a water bath at 300 r / min and 60 °C for 1.5 h to dissolve it.

[0036] (3) Finally, move it to a magnetic stirrer and add a small amount of PDMS (1 wt%). Stir at 800 r / min and 60 °C for 4 h to obtain a PS-1.75 composite film coating liquid.

[0037] (4) Adjust the coating knife to set the thickness of the coating solution to 500 μm, 1000 μm, 1500 μm and 2000 μm, and then apply the coating solution to the aluminum substrate that has been polished by sandpaper.

[0038] (5) Heat the aluminum heating table to 90 °C and place the scraped sample on it to allow it to cure for about 15 min.

[0039] (6) The cured samples were moved to a hot press and heated at 10 MPa and 180 °C for 2 h. Finally, PS-1.75 composite films with thicknesses of 25 μm, 55 μm, 80 μm, and 115 μm were formed.

[0040] In addition, a PVDF film with a thickness of ~115 μm was prepared using the same preparation method as above and used as a control group.

[0041] Figure 4 The SEM images of PS-1.75 composite films of different thicknesses prepared in Example 2 of the present invention are shown below. Figure 4 It can be seen that the thickness of the scraped solution is 500 μm, 1000 μm, 1500 μm and 2000 μm, and the thickness of the prepared composite films are 25 μm, 55 μm, 80 μm and 115 μm, respectively.

[0042] Figure 2 (d)-(h) are optical performance diagrams of PS-1.75 composite films and PSx composite films with thicknesses of 25 μm, 55 μm, 80 μm and 115 μm, respectively, prepared in Example 2 of the present invention. Figure 2 It can be seen from (d)-(f) that as the thickness of the PS-1.75 sample increases, the average reflectivity increases from 80% to 84%, and the average emissivity remains unchanged at ~97%. It can be seen that thickness is also one of the important factors affecting the solar reflectivity of the composite film. Figure 2 (g)-(h) It can be found that the reflectivity and emissivity of PS-1.75 film are greatly improved after adding ST particles compared with pure PVDF. The significant increase in emissivity may be caused by the bending and stretching vibrations of CF and CH functional groups in PVDF and the lattice vibrations of Sr-O and Ti-O bonds in ST.

[0043] Table 1 Thermal conductivity, thermal diffusion coefficient, specific heat capacity, and relative density of PS-1.75 composite membrane with a thickness of 115 μm and PVDF film.

[0044]

[0045] Table 1 shows the thermal conductivity, thermal diffusion coefficient, specific heat capacity, and relative density of the PS-1.75 composite film with a thickness of 115 μm and PVDF with a thickness of 115 μm prepared in Example 2 of the present invention. It can be seen that the thermal conductivity of the PS-1.75 composite material is about 10 times higher than that of pure PVDF. The reason for the high thermal conductivity of the composite material may be that the filling of ST particles reduces the interfacial thermal resistance of PVDF and the disordered state between the molecular chains, thereby promoting the heat transfer of phonons. In order to verify that the PS-1.75 composite film has good thermal conductivity, a finite element simulation (FEM) model was established in the simulation software COMSOL, and the heat transfer behavior of the PS-1.75 and PVDF composite films was simulated. First, in the membrane model, a boundary heat source is defined on one edge, and the heat flow is transferred from one part to another for 1 s; Figure 5 As shown in (a), the temperature of the PS-1.75 composite membrane and the PVDF membrane along the specified direction is calculated simultaneously. The calculation results of PS-1.75 are shown in Figure 5(c) and Figure 5 (d), Calculation results of PVDF Figure 5 (e) and Figure 5 (f) The results show that during the entire heat conduction process, the heat transfer rate of the PS-1.75 composite membrane is faster than that of pure PVDF, and after 1 s of heat transfer, the temperature distribution of the PS-1.75 composite membrane is wider; in addition, Figure 5 (b) It can be seen that compared with the PVDF membrane, the temperature of the PS-1.75 composite membrane at 2.5 cm from the heat source is higher during the entire heat transfer process, which proves that the PS-1.75 composite membrane has efficient heat transfer capability. This may be due to the interaction between the highly thermally conductive ST particles, which reduces the interfacial thermal resistance and promotes the heat transfer of phonons, thereby improving thermal conductivity.

[0046] Example 3 Temperature comparison of aluminum sheet samples coated with PS-1.75 with a thickness of ~115 μm, aluminum sheet samples coated with PVDF with a thickness of ~115 μm, aluminum sheet samples coated with commercial white paint with a thickness of ~115 μm, and aluminum sheet samples in outdoor cooling tests: Schematic diagram of the test box used in the test and photos of the test site, such as Figure 6 (a). The material of the test box is polystyrene with thermal insulation effect, and its surface is also covered with a layer of Al film to reflect sunlight. During the test, the upper surface of the test box also needs to be covered with a layer of PE film, which is used to reduce convection with the outside air, thereby reducing the impact of the external environment on the test results; the test box also contains two thermocouple probes, one located on the lower surface of the sample and the other located in the center of the cavity, which are used to measure the temperature of the sample surface and the air in the cavity. The test was carried out from 10:30 to 14:00 on July 22, 2023. The test results are as follows Figure 6 As shown in (b)-(g). Figure 6 (b) and Figure 6 (e) Describes the surface temperature (including: PS-1.75 surface, PVDF surface, Al surface) and cavity temperature (including: PS-1.75 cavity, PVDF cavity, Al cavity) of all test samples, as well as the sub-ambient temperature. Figure 6 (b) and 6 (c), the average surface temperature of PVDF is ~6 ℃ and ~1.2 ℃ lower than the average surface temperature of Al and the average sub-ambient temperature, respectively, while the average surface temperature of PS-1.75 is ~20.2 ℃ and ~14.5 ℃ lower than the average surface temperature of Al and the average sub-ambient temperature, respectively. Figure 6(e) and (g), the average temperature in the PVDF cavity is -1.2°C and 4.6°C lower than the average temperature in the Al cavity and the sub-ambient average temperature, respectively; while the average temperature in the PS-1.75 cavity is 7.2°C and 12.7°C lower than the average temperature in the Al cavity and the sub-ambient average temperature, respectively. In addition, we also conducted outdoor cooling tests on samples coated with ~115 μm thick PS-1.75 aluminum sheets and samples coated with ~115 μm thick commercial white paint. The test results are shown in the figure. Figure 7 As shown. Figure 7 From (a) to (b), we can see that, with Al as the control sample, the surface temperature and the cavity temperature of the PS-1.75 sample decreased by an average of ~17.7°C and ~6.3°C, respectively, while the surface temperature and the cavity temperature of the white paint sample decreased by an average of ~13.2°C and ~3.1°C, respectively. This shows that the PS-1.7 composite film has a good cooling effect.

[0047] Example 4 Temperature drop performance of PS-1.75 composite film with a thickness of ~115 μm in outdoor electric vehicle charger application scenario: The preparation method of PS-1.75 radiative cooling composite film is as described in Example 2. In order to further confirm the cooling performance of PS-1.75 composite film, the temperature of the covered and uncovered parts of the electric vehicle charger PS-1.75 was recorded using infrared images, such as Figure 8 (a). Figure 8 (b) It can be seen that before the charger was exposed to sunlight, the temperature difference between the covered and uncovered surfaces was only 0.5°C, that is, the temperature difference between the PS-1.75 covered point P1 and the uncovered point P2 was ~0.5°C. Figure 8 As shown in (c), after the charger was exposed to the sun for 1 minute, the temperature difference between the P1 point covered by the PS-1.75 composite film and the P2 point not covered reached 4.7 ° C. After 15 minutes of exposure, the temperature difference between the P1 point covered by the PS-1.75 composite film and the P2 point not covered reached 13.4 ° C. It can be seen that the PS-1.75 composite film we prepared has a good cooling effect. Afterwards, the PS-1.75 film was removed and continued to be exposed to sunlight. The temperatures of the P1 point and the P2 point were recorded at five stages: 0 s after removal, 1 s after removal, 5 s after removal, 8 s after removal, and 15 s after removal, as shown in Figure 2. Figure 8 As shown in (d). When the PS-1.75 composite film is removed for 0 s, it can be seen that the area covered by the PS-1.75 composite film is the "green area"; 15 s after removal, the temperature of the area previously covered by PS-1.75 increases rapidly to 43.2°C, which further proves that the PS-1.75 composite film has excellent cooling performance.

Claims

1. Preparation method for high thermal conductivity radiation cooling composite film, It is characterized in that The steps include: (1) NN dimethylformamide, KH570 and strontium titanate powder are mixed and dispersed to obtain a modified strontium titanate dispersion; (2) Add PVDF powder to the strontium titanate dispersion, heat and dissolve it, then add PDMS, and stir evenly to obtain a PSx composite membrane coating solution; (3) The PSx composite film coating liquid is coated on the substrate, and after being cured on a heated aluminum stage, it is placed in a hot press to dry, thereby obtaining a composite film for high thermal conductivity radiation cooling.

2. The method for preparing a high thermal conductivity radiation cooling composite film according to claim 1, It is characterized in that In step (1), the mass ratio of NN dimethylformamide, KH570 and strontium titanate powder is 10:0.1-0.2:0.5-1.75; preferably, the mass ratio of NN dimethylformamide, KH570 and strontium titanate powder is 10:0.2:1.

75.

3. The method for preparing a composite film for high thermal conductivity radiation cooling according to claim 1, It is characterized in that The dispersion in step (1) is carried out in a cell crusher, and the dispersion time is 5-20 min.

4. The method for preparing a high thermal conductivity radiation cooling composite film according to claim 1, It is characterized in that In step (2), the mass ratio of the added amount of PVDF powder to the strontium titanate powder is 0.5-1.

75.

5. The method for preparing a composite film for high thermal conductivity radiation cooling according to claim 4, It is characterized in that The PVDF powder is added to the strontium titanate dispersion while stirring, the stirring speed is 200-500 r / min, the working temperature is 60-80 °C, and the stirring time is 1-2h.

6. The method for preparing a composite film for high thermal conductivity radiation cooling according to claim 1, It is characterized in that In step (2), the amount of PDMS added is 0.1-1% of the PVDF powder.

7. The method for preparing a composite film for high thermal conductivity radiation cooling according to claim 1, It is characterized in that In step (3), the substrate is a metal aluminum plate polished by sandpaper; The working temperature of the aluminum table is 80-90 ℃; the working parameters of the hot press are 150-180 ℃, 8-10 MPa, 1-2 h.